IS IT TIME FOR THE INTRODUCTION OF SELF-ASSESMENT OF RESTRICTIVE AGREEMENTS INTO SERBIAN COMPETITION LAW? - Fišer-Šobot, Sandra (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
A working group for drafting the new Law on Protection of Competition was formed in 2018. One of the issues raised was whether the legal norms regulating individual exemptions of restrictive agreements should be amended. In other words, it was discussed whether the system of notification of restrictive agreements for individual exemption should be retained or self-assesment of restrictive agreements should be introduced. Another suggested alternative was to allow undertakings to decide if they want to self-asses their agreements or to request individual exemption from the Commission for Protection of Competition. In this paper, the author analyses advantages and shortcomings of both systems, identifies open questions in relation to the system of self-assesment and proposes posible solutions de lege ferenda.